Evolutifon of decision support system architectures: applications to land planning and management in Cuba - Segrera, Saddys (2003)
The main objective of this paper centers on reviewing the evolution of Decision Support System´s (DSS) architectures, particularly as they apply to natural resources. Today it is difficult to conceive the existence of a rural planning automated system that doesn't include spatial analysis functionality and that does not consider the integrated use of different analytical modules. This wider range of functions allow for solving problems from resource and environmental management. Geographical Information Systems (GIS), automated land evaluation, multi-criteria participatory analysis in decision making are but the most salient technologies in a DSS. DSS have evolved; their architecture, mode of implementation, as well as their functionality and the incorporation of new computational techniques have advanced lately. In the particular case of Cuba,the first steps in materializing this evolution have begun. At present, the National Sugar Cane Research Institute (INICA)leads a research project oriented towards the development and building of a dedicated DSS for sugar cane cropping.This is conceived as an integrated SDSS (Spatial DSS)to support decision -making and multiple problem- solving in such a fundamental productive activity such as sugar cane agriculture in Cuba.